See the road well : shaping East Timor's frontier - Sugget, Neil (Pandanus ; Marston [distributor], 2005)
In 1999, Neil Sugget was selected to lead and train Australian Customs officers who volunteered to assist in creating a border service in East Timor, following the conflicts that had erupted during the popular vote for independence. This is his story of working with the East Timorese and the many different nationalities of the United Nations Transitional Authority.